Error analysis of subject verb agreement in present simple third person singular on written sentences with A2.2 EFL students - Torres Merino, José Fabián (2021)
This research is aimed at analyzing the written subject-verb agreement (SVA) errors in present simple in third person singular made by high school students to know the possible sources for these errors and design or plan the most appropriate input to support students to overcome these difficulties. The corpus for this study comprises 15 participants and 366 writing samples obtained from the tasks responses to identify, classify, quantify, and determine the possible sources of errors. The methodology was conducted through a descriptive research design, and it was focused on the qualitative and quantitative approaches. Later, the collected errors were classified conforming to Dulay, Burt, and Krashen's (1982) Surface Strategy Taxonomy, which gathers errors with omission, addition, misformation, and misordering. Likewise, the analysis of the results to know the possible sources for these errors is based on prominent studies from specialists in this field. The results reveal that the most common error that students make deals with misformation, followed by omission and misordering errors, whereas addition is the least frequent error; thus, most of the errors are intralingual as the students apply rules inadequately or incompletely. Further, other errors are interlingual since the errors committed by the participants are from the negative transfer of their mother language. Lastly, the context of learning is another significant source of error considered in this paper. Based on the information, teachers could detect students' needs and design the most effective and optimal input to overcome this issue from the results.